Implementation of Islamic Values in the Education of Children Aged 4-6 Years - Fahriansyah, Fahriansyah; Ruslan, Muhammad; Rahman , Abd (STAI Publisistik Thawalib Jakarta, 2025)
The implementation of Islamic values in children's education is an important effort to form good character and morals from an early age. Education based on Islamic values provides a strong foundation for children to understand the concepts of kindness, honesty, discipline, and responsibility. The purpose of this study is to find out how to apply Islamic values in children's education in Al Fikh Orchard Taman Setia kindergarten, Klang, Malaysia. This research uses a qualitative method with observation, interview, and documentation data collection techniques. The results of the research on the implementation of Islamic values in children's education are learning that integrates Islamic teachings, such as the concept of monotheism, worship, noble morals, and good social relationships, will guide children in living a life in accordance with religious principles. The implementation of habituation, example, and storytelling methods at Al Fikh Orchard Kindergarten is effective in instilling Islamic values in early childhood, with support from schools and families